Assessing performance of the Healthcare Access and Quality Index, overall and by select age groups, for 204 countries and territories, 1990–2019: a systematic analysis from the Global Burden of Disease Study 2019 - Haakenstad, A (Elsevier BV, 2023)
10.1016/S2214-109X(22)00429-6